2012
DOI: 10.1007/s00246-012-0462-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ventriculotomy on Right-Ventricular Remodeling in Hypoplastic Left Heart Syndrome: A Histopathological and Echocardiography Correlation Study

Abstract: The objective of this study was to compare histopathological changes in hypoplastic left heart syndrome right ventricles (RV) of patients undergoing Sano and modified Blalock-Taussig (MBT) shunt and correlate them with echocardiographic findings. Myocardial tissue samples were obtained from hearts with Sano or MBT shunts after transplantation or at autopsy. Histologic sections were reviewed manually and by automated digital image analysis. Velocity vector imaging was performed on echocardiogram images obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In this study, one of the 10 cardiac atlas modes captured the shape remodelling differences between the RVPA conduit and MBT shunt groups and corresponded to increased sphericity and dilatation of the heart. The formation of the fibrotic scar after stage II surgery might cause reduced regional growth in the scar region relative to the remote myocardial wall, as previously described in echocardiographic and postmortem studies [17], leading to the observed change in the shape of the ventricle. The effects of pulmonary regurgitation through a non-valved conduit may also contribute to this difference in shape.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In this study, one of the 10 cardiac atlas modes captured the shape remodelling differences between the RVPA conduit and MBT shunt groups and corresponded to increased sphericity and dilatation of the heart. The formation of the fibrotic scar after stage II surgery might cause reduced regional growth in the scar region relative to the remote myocardial wall, as previously described in echocardiographic and postmortem studies [17], leading to the observed change in the shape of the ventricle. The effects of pulmonary regurgitation through a non-valved conduit may also contribute to this difference in shape.…”
Section: Discussionmentioning
confidence: 68%
“…Postmortem studies have shown that the scar remains stable in size irrespective of patient age and consists of fibrosis and ventricle wall thinning [17]. Echocardiographic studies have found wall motion abnormalities localized to the ventriculotomy site [18], with altered contractility occurring only after removal of the conduit and formation of a scar.…”
Section: Discussionmentioning
confidence: 99%
“…Some have hypothesized that this would lead to local or global RV injury. 13 Ballweg and colleagues reported a higher degree of impaired RV function in those children receiving an RVPAS as compared to a MBTS; 8 however, the use of the two shunt types was not randomized, and those receiving the RVPAS were more likely to have aortic atresia. Frommelt and colleagues found that, on the echocardiogram performed between 14-months and the Fontan operation, the MBTS group had stable indexed RV volumes and ejection fraction, whereas the RVPAS group had increased RV end-systolic volume and decreased RV ejection fraction (RVEF).…”
Section: Discussionmentioning
confidence: 99%
“…This leads to ventricular scarring (Wong et al 2016). An autopsy study has demonstrated that the ventriculotomy scar is associated with increased fibrosis and thinning of the surrounding myocardium, and this effect does not seem to regress with time (Menon et al 2013). Reverse remolding of the surrounding myocardium can further affect function, since myocardial cells are needed to generate ventricular wall thickening.…”
Section: The Physiology Associated With the Rvpa Conduitmentioning
confidence: 99%
“…A scarred myocardium will not contract in the same way as the rest of the healthy myocardium (Menon et al 2013). Depending on the severity and thickness of the myocardial injury, the myocardial contractions will be variably affected (Rácz et al 2015).…”
Section: The Physiology Associated With the Rvpa Conduitmentioning
confidence: 99%